Teaching Through Turmoil: Social Studies Teachers and Local Controversial Current Events. (2nd July 2016) - Swalwell, Katy; Schweber, Simone
Abstract: The protests against the Budget Repair Bill in Wisconsin during the spring of 2011 provide a powerful moment in which to examine social studies teachers' curricular, pedagogic, and personal political decisions in the context of a local, controversial current event. We engaged 7 middle and high school social studies teachers from small and large, liberal and conservative communities who participated in the protests in in-depth, semi-structured interviews using direct prompts rooted in critical incident scaffolding and open questions in keeping with oral history traditions. The teachers' stories reveal the profound significance of that moment in their lives, the ways in which teaching through turmoil deepened their political awareness and activism, a range of factors influencing their decisions of whether or not to disclose their opinions to their students, the importance of the need for "balanced" teaching of controversial issues, and the ways in which they feel their voices have been silenced in the aftermath of the legislation.